The impact of the implementation of the two-dose varicella vaccine immunization strategy in Quzhou: A retrospective birth cohort study - Tingcui Wen; Quanjun Fang; Canya Fu; Canjie Zheng; Jie Pan; Biyun Zheng; Wenjie Xu; Zhiying Yin (Taylor & Francis Group, 2024)
Varicella is a vaccine-preventable disease caused by the varicella zoster virus (VZV), but the varicella incidence among children has increased in recent years. This was a retrospective birth cohort study based on the Zhejiang Provincial Immune Information System (ZJIIS) and the China Information System for Disease Control and Prevention (CISDCP) in Quzhou. A total of 1,291 clinically diagnosed varicella cases born from 2009 to 2014 were collected during 2009-2023, which were analyzed the impact of changes in vaccination strategy on the incidence of varicella based on the Cox-proportional hazards model. It was observed that the onset age of varicella shifted to the older age group and later to 9-11 years. After the change to the two-dose varicella vaccination strategy, the population affected by varicella was concentrated among students and received more than one dose of live attenuated varicella vaccine (VarV). Based on the Coxproportional hazards model and adjusting for all covariates, the risk of varicella infection in children decreased after the introduction of the two-dose varicella vaccination strategy (HR = 0.04, 95% CI: 0.03-0.05). Meanwhile, the Kaplan-Meier curves also showed that the hazards were lower after the change in vaccination strategy. It is recommended that two doses of VarV should be included in the national immunization schedule and that full vaccination should be completed approximately four years after the first dose.